2018
DOI: 10.26442/terarkh201890796-101
|View full text |Cite
|
Sign up to set email alerts
|

Successful experience of treatment of a patient with generalized non-GCB- DLBCL using the R-mNHL-BFM-90 protocol with lenalidomide: case report and review of literature

Abstract: Diffuse large B-cell lymphoma is categorized by gene expression profiling into germinal center (GCB) and activated B-cell (ABC) subtype, also referred to as non-germinal center B-cell (non-GCB) by immunohistochemistry. ABC DLBCL is characterized by NF-κB pathway activation and high expression of IRF4/MUM1, a key transcription factor in B cell differentiation. Patients with ABC DLBCL have a significantly worse outcome when treated with standard chemotherapy (R-CHOP). Lenalidomide have shown activity in the ABC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In our clinic, the use of the intensive block program R-mNHL-BFM-90 resulted in the improved treatment of a group of DLBCL patients with unfavorable prognosis factors [ 22 ]. A retrospective evaluation of the results showed that in most cases of treatment failure, the tumor belonged to the postgerminal immunohistochemical variant of DLBCL (non-germinal center B-cell (non-GCB)-DLBCL), a molecular analog of the ABC-DLBCL subtype [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our clinic, the use of the intensive block program R-mNHL-BFM-90 resulted in the improved treatment of a group of DLBCL patients with unfavorable prognosis factors [ 22 ]. A retrospective evaluation of the results showed that in most cases of treatment failure, the tumor belonged to the postgerminal immunohistochemical variant of DLBCL (non-germinal center B-cell (non-GCB)-DLBCL), a molecular analog of the ABC-DLBCL subtype [ 23 ].…”
Section: Introductionmentioning
confidence: 99%